Simulation of Rainwater Harvesting Potential to Satisfy Domestic Water Demand Based on Observed Precipitation Data in Jakarta - Rista Hernandi Virgianto; Qurrata Ayun Kartika (Journal of Engineering and Technological Sciences, 2021)
Jakarta as the most populous urban center of Indonesia has a major problem related to clean water availability for the domestic needs of its residents, who mostly depend on the extraction of groundwater. The rooftop rainwater harvesting (RRWH) system is a solution to reduce the use of groundwater to satisfy domestic water needs. This study used demographic data and precipitation observation data from the rain gauge network in Jakarta to simulate the water supply from rainwater harvesting from 2010 to 2019 in each municipality. Three simulations were carried out to calculate the percentage of domestic water demand (DS) satisfied by RRWH based on the proportion of residential areas installed with RRWH (RA). The results showed that an RA value of 0.2 produced the lowest DS (approximately 11% to 18.7%), while an RA value of 0.3 produced a higher DS (approximately 16.3% to 28%). An RA value of 0.4 resulted in a DS of around 21.8% to 37.4%. Overall, the RRWH system could provide up to 30% of domestic water demand on average, with South Jakarta having the highest fulfillment of water needs with an average of 28% based on the three simulations, while Central Jakarta had the lowest with 16.4%.